2010
DOI: 10.1016/s1734-1140(10)70325-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of terfenadine and ketoconazole-induced QT prolongation in conscious telemetered guinea pigs

Abstract: Abstract:Terfenadine and ketoconazole are the most widely used positive reference agents in non-clinical cardiac repolarization safety studies. The aim of the present study was to evaluate the effects of terfenadine, ketoconazole and their combination on QT prolongation using conscious guinea pigs. Conscious telemetered guinea pigs were orally administered terfenadine (50 mg/kg), ketoconazole (200 mg/kg) or a combination of the two, and effects on QT were recorded using a telemetry system. The QT correction wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Measurement of ECG parameters following administration of terfenadine at different concentrations. Previous studies have reported that terfenadine prolonged the QT interval in a dose-dependent manner (10,14,15). In the present study, the impact of terfenadine on the QT interval was also examined.…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Measurement of ECG parameters following administration of terfenadine at different concentrations. Previous studies have reported that terfenadine prolonged the QT interval in a dose-dependent manner (10,14,15). In the present study, the impact of terfenadine on the QT interval was also examined.…”
Section: Methodsmentioning
confidence: 80%
“…A recent study also reported that the use of terfenadine alone did not produce an effect on the RR and QT intervals, QRS complex or heart rate in guinea pigs. However, a combined oral dose of terfenadine and ketoconazole significantly prolonged the RR and QT intervals and decreased the heart rate in a time-dependent manner (10). In another recent study, to detect whether the effect of terfenadine on K + channels was separated from the antihistaminic activity, a series of analogs of terfenadine were prepared with structural variations, and the results demonstrated that the ability to inhibit K + channels was generally in parallel with the antihistaminic activity (11).…”
Section: Introductionmentioning
confidence: 99%
“…Since this enzyme is a major metaboliser of many QT prolonging drugs, this reduction in CYP3A activity can lead to altered pharmacokinetics and hence a greater plasma concentration of either drug (Zhi et al 2015 ). This link between inhibition of drug metabolism and proarrhythmia has been observed across multiple studies including reports that ketoconazole, erythromycin, diltiazem, itraconazole and grapefruit juice — all inhibitors of cytochrome P450 enzymes — have resulted in increased serum concentration of terfenadine, halofantrine and cisapride, leading to QT prolongation and TdP (Charbit et al 2002 ; Paris et al 1994 ; Pohjola-Sintonen et al 1993 ; Rajput et al 2010 ; Thomas et al 1998 ). This phenomenon has also been detected in larger cohorts where coadministration of ketoconazole with domperidone was found to triple the plasma concentration of domperidone, exacerbating QTc prolongation to clinically significant levels, over and above that observed for either agent alone (Boyce et al 2012 ).…”
Section: Drug Coadministrationmentioning
confidence: 86%
“…Several drugs have minor or major unwanted side effects. Early detection of these drawbacks was performed by safety pharmacology studies which majorly impact cardiovascular system (Rajput et al, 2010). The cardiovascular system is examined for alterations in ventricular depolarization and repolarization, as well as the QT interval, which is de ined as the time between the commencement of the QRS complex and the end of the electrocardiogram's T wave (ECG) (Redfern et al, 2003) and (Malik and Camm, 2001).…”
Section: Discussionmentioning
confidence: 99%